Void formation in resin transfer moulding - Lowe, Julian Robert (1993)
In recent years interest has grown in the use of composite components within the automotive industry. Fibre reinforced plastic (FRP) components are of particular interest to the industry, since lower tooling costs and part consolidation can be utilised, whilst lighter, stiffer components can be produced. Several methods are available to produce FRP components at high volumes, including compression moulding (using dough and sheet moulding compounds), reinforced reaction injection moulding (RRIM) and liquid moulding processes (resin transfer moulding (RTM) and structural reaction injection moulding (SRIM)). RTM is a closed mould process, which is widely used to produce components economically in low volumes using matched moulds to produce two good surfaces. The absence of a high volume manufacturing technology, however, has impeded the acceptance and advance of RTM within the automotive industry.